The Chronicles of Myelodysplastic/ Myeloproliferative Legacy - Chronic Myelomonocytic Leukemia - Sugathan, Vinu; Abraham, Latha K; Paul, Mobin (Annals of Pathology and Laboratory Medicine, 2020)
Chronic myelomonocytic leukemia is a heterogeneous syndrome with features of both myelodysplastic syndromes (MDS) and myeloproliferative neoplasms (MPN). The varied clinical presentations add to the distinctiveness of the disease. This heterogeneity should invigorate the search for reliable predictors of evolution and progression of disease. We report a case series from a tertiary care centre in Kerala, South India. This was a retrospective observational study of all cases of CMML, which was diagnosed in the departments of Pathology and Clinical Haematology & Haemato- oncology of our institution between January 2017 to May 2020. The clinical presentation, laboratory investigations, and treatment details were noted. Nine cases of CMML were encountered during the study period. The mean age of study subjects was 70.4 years with a female predilection. Fever and weight loss were the most common clinical presentations. Four patients were classified as CMML- 2, three patients as CMML- 1, and two as CMML- 0. Based on the WBC count, five patients were classified as dysplastic and four as proliferative subtypes. Two patients had grade 1/3 (one case each of CMML- 2 and CMML- 1) and one patient had grade 2/3 fibrosis (a case of CMML- 1) in the bone marrow. Thirty-three percentage patients had clonal cytogenetic abnormalities, the commonest being trisomy 8. Renal function was deranged in three patients and two patients had a deranged liver function and hepatomegaly. Four patients underwent treatment with hypomethylating agents or cytoreduction with hydroxyurea. One of the patients (CMML- 2 with marked leucocytosis) succumbed to disease.